Phosphorous esters of 2,13-dihydroxy-7a,14c-dihydronaphtho[1 ',2 ': 4,5]furo[3,2-d]furan - (:unkn) unknown (FREUND PUBLISHING HOUSE LTD, 1999)
2,13-dihydroxy-7a,14c-dihydronaphtho[1',2':4,5]furo[3.2-d]furan prepared from glyoxal bisulphite and 2,7-dihydroxynaphthalene was reacted with, C6H5PCl2, C6H5POCl2 and Br-C6H4OPOCl2 to produce its phosphorous esters. The structures of the products were investigated by MS, FTIR, H-1-NMR, C-13-NMR, and P-31-NMR. Although C6H5PCl2 gave a compound with a new ring containing phosphorous atom, C6H5POCl2 and Br-C6H4OPOCl2 resulted acyclic phosphorous esters.